Study and define the criteria for evaluating the performance of Unsignalized intersections according to HCM 2016 methodology - شحاده , حلا; أكرم رستم (Latakia University Journal -Engineering Sciences Series, 2024)
Unsignalized intersections (TWSC: Two Way Stop-Control) constitute a large percentage of intersections within cities and their suburbs. They are characterized by the presence of two directions of movement, major and minor. Drivers on the major street have priority over drivers on the minor street. In this article, the effect of conflicting movements was studied using the HCM 2016 methodology (Highway Capacity Manual) on the performance of TWSC intersections. A four-leg intersection in Latakia city was studied by conducting field observation of the intersection and collecting geometric and traffic data to determine the criteria that most affect traffic movement. We calculated control delay, queue lengths, and level of service for each minor movement and comparing them to reality. The results showed that the intersection operates with a very good level of service, with short delays, and that a queue rarely forms with more than one vehicle, with the exception of one minor leg, and the results were acceptably close to reality.